Participatory planning handbook for people-oriented forestry - Philippines. Department of Environment and Natural Resources. Upland Development Program (Quezon City DENR and Ford Foundation, 1994)
Contains detailed procedures and tools to help implementors and farmers plan their farms and community. Farm planning and community planning forms the two main divisions of the book
Keywords: Social forestry programs -- Philippines -- Handbooks, manuals, etc; Forest management -- Planning -- Philippines; Participant observation